Checkmate: a real-time tracking system using face recognition and geofencing - Mohd Sulaiman, Muhammad Sufyan Syahmi (2025)
CheckMate is a mobile app aiming to revolutionise teacher attendance in schools, eliminating the cumbersome punch-card systems of the past, replacing them with face recognition and geofencing. The system promotes safe and accurate attendance marking by identifying who the user is and verifying their location in real-time. CheckMate was developed using the Extreme Programming (XP) methodology, which emphasises short iterations of development, frequent stakeholder feedback, and usability testing. The system incorporates a mobile interface for teachers focusing on drawing as little attention as possible to the attendance process; an analytical dashboard for staff and administrators; and extensive data logging for study record retention. Testing has shown consistent reliability, with 87.5% of users stating they had no issues in marking attendance and 100% geofencing fidelity. CheckMate also has the limitations of facial recognition being sensitive to lighting issues, however CheckMate provides a sustainable pathway to eliminating time-consuming administrative tasks and reducing fraud. Future advancements may include multi-platform support and analytic dashboards. The development of CheckMate and the potential its provides to the educational administration sector demonstrates the promise of developing biometric and location-based technologies.